LEARNING WHILE LAUGHING: TRENDS, STRATEGIES, AND THE IMPACT OF HUMOR IN LEARNING THROUGH A BIBLIOMETRIC ANALYSIS - Amiruddin, Amiruddin; Irhamni, Hadi (International Journal of Education, 2025)
A pleasant learning environment enhances students' motivation and participation in the learning process. As a pedagogical tool, humor helps enhance motivation, increase student engagement, and create a positive and enjoyable learning atmosphere. The research aims to uncover research trends on humor in learning, strategies, and the impact of using humor in learning. To achieve this objective, this study utilizes the systematic literature review method from two databases, namely Eric and Springer. The results of the bibliometric analysis-based research reveal that the research trends on humor in learning from 2019 to May 20, 2023, indicate an average of 5.3 publications per year. Research on humor in learning is conducted in countries such as the United States, Turkey, Germany, Taiwan, Dardania, France, Hungary, Indonesia, Iran, Italy, Japan, Romania, New Zealand, and South Africa. No standardized strategies for using humor in learning were found.  Nevertheless, the use of humor must be adjusted to the students' cultural backgrounds, selected at the right time, integrated into the curriculum, and may utilize media such as humorous images and videos. The use of humor in teaching has positive impacts, such as increasing student engagement, confidence, critical thinking skills, teacher-student relationships, and learning motivation. However, inappropriate humor can disrupt the learning process, increase negative bias, and create discomfort and negative perceptions among students.